2019
DOI: 10.1088/1367-2630/ab59fe
|View full text |Cite
|
Sign up to set email alerts
|

There is no general connection between the quantum speed limit and non-Markovianity

Abstract: The quantum speed limit (QSL) sets a bound on the minimum time required for a quantum system to evolve between two states. For open quantum systems this quantity depends on the dynamical map describing the time evolution in presence of the environment, on the evolution time τ, and on the initial state of the system. We consider a general single qubit open dynamics and show that there is no simple relationship between memory effects and the tightness of the QSL bound. We prove that only for specific classes of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…This connection was later studied in more detail, and it was found that the speed-up is not always dependent on the information backflow and can sometimes be present without any non-Markovian effects [10]. In this case, the presence of information backflow coincides with the loss of P-divisibility.…”
Section: Open Quantum Systems Dynamical Maps Divisibility and Qslmentioning
confidence: 99%
See 2 more Smart Citations
“…This connection was later studied in more detail, and it was found that the speed-up is not always dependent on the information backflow and can sometimes be present without any non-Markovian effects [10]. In this case, the presence of information backflow coincides with the loss of P-divisibility.…”
Section: Open Quantum Systems Dynamical Maps Divisibility and Qslmentioning
confidence: 99%
“…In [ 4 ], it was shown that, for an amplitude damping system, as given by master Equation ( 2 ) with and , the QSL is directly dependent on the information backflow as where and is the Breuer–Laine–Piilo (BLP) non-Markovianity measure, as given by This connection was later studied in more detail, and it was found that the speed-up is not always dependent on the information backflow and can sometimes be present without any non-Markovian effects [ 10 ]. In this case, the presence of information backflow coincides with the loss of P-divisibility.…”
Section: Open Quantum Systems Dynamical Maps Divisibility and Qmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum speed limit as a measure of non-Markovianity, and its connection with the hierarchy of quantum correlations of composite quantum system [28,29] are discussed in [30,31]. Even though quantum speed limit time seems to identify the information backflow due to the non-Markovianity, in [30] it is shown that there exists no simple connection between non-Markovianity and speed limit time. This raises the question of whether there is a quantum concept of memory that is better indicated by the quantum speed limit.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of QS in the context of open quantum systems [6] was developed in the last decade [7][8][9]. The concept of QS has been used to shed light into various facets of quantum information [10,11], open systems [12][13][14][15], control of quantum systems [16] and quantum thermodynamics [17,18]. Further, using causality and thermodynamics, the important Bremermann-Bekenstein bound [19,20] relates the energy cost per bit of information to the QSL time.…”
Section: Introductionmentioning
confidence: 99%